190 Association between carotid distensibility and heart rate variability in older age. (4th June 2021) - Fornasiero, Massimiliano; Webber, Matt; Moon, James; Friberg, Peter; Hughes, Alun; Captur, Gaby
Abstract : Background: Heart rate variability (HRV) is a prognostically relevant biomarker of autonomic regulation. Carotid stiffening that may precede hypertension, could theoretically inhibit the baroreceptor reflex, resulting in cardiac autonomic dysfunction and abnormal HRV indices. We investigated the association between carotid artery distensibility (the inverse of carotid arterial stiffness) and HRV in an older age population-based cohort. Method: Participants were from the 1946 Medical Research Council (MRC) National Survey of Health and Development (NSHD) British birth cohort. Carotid intima media thickness (cIMT) and carotid artery distensibility (exposures) were measured by ultrasound. Calibrated images and dedicated software automatically measured carotid distensibility, while semi-automatic edge detection software was used to measure cIMT. Time- and frequency-domain analysis of each participant's 6-minute resting 3-lead tachogram at age 60-64 years yielded the following HRV biomarkers (outcomes): standard deviation of normal-to-normal beats (SDNN); root mean square of successive differences (RMSDD); HRV triangular index; high-frequency (HF) power; low-frequency (LF) power; total power spectral density (PSD); power spectral density squared; normalised LF and HF power and HF:LF ratio . Generalized linear models (glm) were used, and adjustment was made for relevant demographic and health-related confounders including BMI, sex socio-economic position and plasma triglyceride levels. Results: A total of 896 participants were included (46.5% men, figure 1 ). On univariate analysis carotid distensibility, but not cIMT, correlated with the following HRV markers: SDNN, total PSD and HRV triangular index (markers of overall variability), RMSDD (marker of parasympathetic activity), HF power and LF power (markers of parasympathetic and sympathetic activity, all p<0.05). These associations persisted in fully adjusted multivariable models ( table 1 ): SDNN beta 0.63; 95% confidence interval (CI) 0.4, 0.9; p<0.001; RMSDD beta 0.60; CI 0.3, 0.9; p<0.001; HRV triangular index; beta 0.13; CI 0.06, 0.19; p<0.001; HF power; beta 8.04; CI 2.3, 13.8; p=0.006; LF power beta 9.86; CI 4.7, 17.0; p<0.012; total PSD beta 25.40; CI 8.8, 43.4; p=0.008. Conclusion: Carotid arterial stiffness in older age is associated with reduced HRV independent of early carotid atherosclerosis (cIMT), hypertension or stroke, potentially through an impaired baroreceptor response. As loss of carotid distensibility can be prevented and loss of HRV predicts cardiovascular mortality, public health policies should implement more and earlier cardiovascular health interventions to maintain carotid distensibility, with HRV as a marker of disease progression. Conflict of Interest: None